Political Protest in Times of Crisis. Construction of New Frames of Diagnosis and Emotional Climate - Sabucedo, José-Manuel; Barreto, Idaly; Seoane, Gloria; Alzate, Mónica; Gómez-Román, Cristina; Vilas, Xiana (Frontiers in Psychology, 2017)
In times of crisis, political mobilisations increase. Many of them compete to impose a determined diagnosis of the situation. This work analyses this issue, taking into consideration two of the movements that have had a greater incidence during the crisis in Spain: The Catalonian National Assembly and the Marches for dignity. The objective is to know how the categories of aggrieved ingroup and outgroup responsible were identified and how both these movements defined the emotional climate at that moment. This work includes two studies. In the first one, an analysis of the categories identified in the manifestos published by these two movements was carried out. The results show that the Marches for dignity constructed a more inclusive ingroup identity and show a more negative emotional climate than the Catalonian National Assembly. The second study includes a sample of 919 participants and non-participants in 2 demonstrations called by those organisations. In this case MANOVAS of 2 (Type of demonstration: Catalonian National Assembly, Marches for dignity) x 2 (Type of participants: participants, non-participants) were performed. Results show that participants in both demonstrations have a higher level of injustice than non-demonstrators. Furthermore, demonstrators in Marches for dignity have a more negative perception of emotional climate than non-demonstrators. However, and contrary to the hypothesis, demonstrators of the Catalonian National Assembly have a more positive perception of emotional climate than non-demonstrators. The work explains these results in the socio-political context in which each of these movements acts and highlights the relevance of comparative investigation designs to further the knowledge of political mobilisation dynamics.